Gender identity on career aspiration to top management among Iranian graduate students of an institution of higher learning - Karami, Roya; Ismail, Maimunah; Md. Sail, Rahim (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
The picture of gender-imbalanced managerial participation has been changing over the past few decades by neo-liberal policies and other affirmative actions. But still, there is a wide gap in top management positions held by men and women. Gender stereotype, glass ceiling and other related factors keep women as a group from attaining top management positions. This study aims to assess the effect of gender identity on aspirations to top management. It also believes that traditional gender role stereotyping would be correlated with gender traditional career aspirations and that masculine subjects would have greater career aspirations to top management than feminine subjects. Many important career decisions are made early during adolescence and studying period, and these decisions affect the rest of a person's life. Therefore, this study concentrates on Iranian graduate students of UPM as a potential population of future workplace. The data were analysed using descriptive statistics, two ways factorial ANOVA and enter method logistic regression. The results showed that masculinity had a significant positive effect on respondents' aspirations to top management. The study results are also useful for educational policy development on the effect of gender role stereotype on career aspiration of students and lecturers in institutions of higher learning.